2018
DOI: 10.15353/cfs-rcea.v5i3.258
|View full text |Cite
|
Sign up to set email alerts
|

Can we eat our way to a healthy and ecologically sustainable food system?

Abstract: The food system is a major contributor to climate change, biodiversity loss, eutrophication and deforestation. This article examines national dietary guidelines as a way to shift dietary patterns in the population toward diets that continue to promote health while being more ecologically sustainable. While some sustainability principles may be inherent in the 2007 Canada’s Food Guide (e.g., an emphasis on plant-based foods), these were not made explicit. As Health Canada undertakes a revision of its national d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…After data extraction, 11 peer reviewed articles remained, all published since 2008. 10,[15][16][17][18][19][20][21][22][23][24] Nine articles were written by RDs, or with a dietitian on the author team. 10,[15][16][17]19,[21][22][23][24] Two were written by other health professionals but with specific and explicit relevance for RDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After data extraction, 11 peer reviewed articles remained, all published since 2008. 10,[15][16][17][18][19][20][21][22][23][24] Nine articles were written by RDs, or with a dietitian on the author team. 10,[15][16][17]19,[21][22][23][24] Two were written by other health professionals but with specific and explicit relevance for RDs.…”
Section: Resultsmentioning
confidence: 99%
“…10,[15][16][17][18][19][20][21][22][23][24] Nine articles were written by RDs, or with a dietitian on the author team. 10,[15][16][17]19,[21][22][23][24] Two were written by other health professionals but with specific and explicit relevance for RDs. 18,20 Sixteen grey literature documents were published since 2004 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ; 15 were written by RDs, or with a dietitian on the author team (this included one who identified as a Nutritionist and is a licensed RD) [25][26][27][28][30][31][32][33][34][35][36]…”
Section: Resultsmentioning
confidence: 99%
“…Dietary guidelines have been proposed as one tool to promote sustainable dietary practices and address the complex challenge of shifting diets (Gussow and Clancy, 1986;Dye Gussow, 1999;Lang, 2017;Lang and Mason, 2017;Seed and Rocha, 2018;Willett et al, 2019). Recent evidence has shown that greater adherence to FBDGs has been correlated with more plant-based diets; further, diets following guidelines were associated with lower health costs, energy intake and environmental impact scores, more deaths averted, and less exposure to pesticides (Kesse-Guyot et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Food based dietary guidelines (FBDGs) are a tool to disseminate the policy guidance given by national governments, and can be the foundation of national dietary education, measurement, and monitoring activities (Seed and Rocha, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation